2012
DOI: 10.1021/jp300187r
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Pathway of CIGSe Nanocrystals for Solar Cell Applications

Abstract: CuIn x Ga 1−x Se 2 nanocrystals synthesized via the hot injection route have been used to make thin film solar cells with high power conversion efficiency. Thus, CuIn x Ga 1−x Se 2 nanocrystals have the potential to provide a low cost and high efficiency solution to harvest solar energy. Stoichiometry control of these nanocrystals offers the possibility of tuning the band gap of this material. It is important to understand how the composition of quaternary CuIn x Ga 1−x Se 2 nanocrystals evolves to control the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…35 Recently, Mahshid Ahmadi et al reported that the CIGSe nanocrystals formed with the binary phases of CuSe and In 2 Se 3 as the primary intermediates. 36 Thus the similar result was expected to complete the conversion to ternary chalcopyrite phase CuGaS 2 from binary compounds as the primary intermediates by increasing the annealing temperature. The formation of CuGaS 2 (CGS) is thermodynamically preferred over the formation of CuInS 2 (CIS) and it has been shown that CuGaS 2 (CGS) crystals can be even grown from an indium solution.…”
Section: Resultsmentioning
confidence: 63%
“…35 Recently, Mahshid Ahmadi et al reported that the CIGSe nanocrystals formed with the binary phases of CuSe and In 2 Se 3 as the primary intermediates. 36 Thus the similar result was expected to complete the conversion to ternary chalcopyrite phase CuGaS 2 from binary compounds as the primary intermediates by increasing the annealing temperature. The formation of CuGaS 2 (CGS) is thermodynamically preferred over the formation of CuInS 2 (CIS) and it has been shown that CuGaS 2 (CGS) crystals can be even grown from an indium solution.…”
Section: Resultsmentioning
confidence: 63%
“…Compared to other amine solvent groups, polyetheramine enhances the attack against the copper, which made the first phase unstable. This resulted in the appearance of binary phase CuSe 2 in the early stages of the reaction (at 3 hr); however, it did not appear later, which indicates that the polyetheramine-based reaction was very rapid [50]- [51]. To further investigate the valence states of four ions, XPS analysis was used to examine elements valence states of 3-hr nanoparticles, as shown in Fig.…”
Section: Characterization Of Structure and Morphology Of Cztse Nanopamentioning
confidence: 99%
“…For our mechanism studies, we first investigated the effect of Sb on the formation of Cu-Se binary compounds, because Cu-Se phases are essential for CIGS formation [11] and evolution of Cu-Se binary phases takes place first as a result of favorable reaction kinetics [8,18,19]. We chose solvothermal process as the model method because CIGS formation pathway in solvothermal synthesis has been proved via the reaction of Cu-Se binary selenide with In and Ga precursors [18].…”
Section: Effect Of Sb On the Cu-se Intermediate Formationmentioning
confidence: 99%
“…Mobile Cu + cations delocalize in Cu 3 SbSe 3 lattice at elevated temperature (e.g., 200 1C) and react with In and Ga precursors to form CIGS with favorable kinetics, due to facilitated mass transfer and high reactivity of Cu + cations. Here, the In and Ga precursor may be the binary selenide complexes [8,24,25] or cations of these two metals [19]. After consumption of Cu in Cu 3 SbSe 3 , the remaining Sb-Se species react with Cu 2 Se to further supply Cu 3 SbSe 3 .…”
Section: Proposed Mechanism For Sb Promoted Cigs Formationmentioning
confidence: 99%